Tafsir Ahkam QS Al-Baqarah 283: Analisis Asbabun Nuzul, Mufrodat, dan Hukum Rahn dalam Muamalah Safar - Nurlelasari, Irma; Bisri, Hasan; Athoillah, M. (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
Qur'an Surah Al-Baqarah (2):283 extends verse 282 on debt transactions, emphasizing justice in muamalah during travel without a contract writer. This study explores the asbabun nuzul of the verse, which, per contextual narrations in Ibn Kathir, was revealed in Madinah to address unsecured debts lacking witnesses, promoting rîhânun maqbûdah (tangible collateral) as a safeguard. Mufrodat analysis covers key terms like amînah ba'dukum ba'dan (mutual trust based on taqwa) and yû'addî alladzî ûtumina amânatahû (obligation to fulfill entrusted debts), forming the basis for tafsir ahkam: rahn is obligatory during travel or without witnesses, concealing testimony is forbidden, and mutual trust is permissible with piety. Employing a qualitative maudhu'i tafsir approach with lafzhiyah (linguistic), historical, and ijtihadi analysis, the research draws from primary sources (Tafsir Ibn Kathir, Jalalain, Al-Munîr) and secondary fiqh texts (Hanafi-Shafi'i schools). Findings affirm rahn's validity in fiqh to protect creditors without exploiting collateral. The contemporary study links the verse to sharia pawn-broking in the digital era, such as Pegadaian Syariah platforms or Islamic fintech (e.g., rahn + murabahah apps). Challenges include verifying virtual assets (NFTs/crypto); solutions involve blockchain for amanah transparency and compliance with OJK/DSN-MUI regulations. The results underscore verse 283's relevance to modern Islamic economics, reinforcing digital muamalah ethics rooted in justice and taqwa. Recommendations include specific fatwas on virtual rahn to prevent hidden riba.